Reconstruction of the Theory of Legal Authority in Islam: A Dialectic between Revelation, Reason, and Social Reality - Abdul Rahman; Muhammad Sopyan; Khairuddin Hasibuan; Manswab Mahsen Abdulrahman (Jurnal Cendikia ISNU SU, 2026)
This study reconstructs the theory of legal authority in Islam by examining the dialectical relationship between revelation, reason, and social reality as the three fundamental epistemological pillars of Islamic legal formation. The study is motivated by the inadequacy of classical hierarchical models of legal authority to fully explain contemporary legal challenges arising from technological advancement, globalization, and increasing social complexity. Accordingly, the research aims to develop a reconstructed theoretical framework that explains how Islamic legal authority is generated through the dynamic interaction of divine revelation, rational interpretation, and empirical social context. This research employs a qualitative library research method using historical, philosophical, and conceptual approaches. Primary sources include the Qur'an, Hadith, classical works of uṣūl al-fiqh, and contemporary scholarship on Islamic legal theory, which are analyzed through critical, comparative, and dialectical methods. The findings demonstrate that revelation remains the supreme source of normative legitimacy, reason functions as the epistemological mechanism for legal interpretation through qiyās, istiḥsān, and maṣlaḥah, while social reality serves as an empirical dimension that continuously shapes contextual legal reasoning through ijtihād. Beyond reaffirming these traditional roles, this study proposes a reconstructed Triadic Dialectical Authority Model, in which legal authority emerges from the continuous interaction among normative legitimacy, rational coherence, and contextual responsiveness rather than from a purely hierarchical relationship. This model offers a theoretical contribution by redefining Islamic legal authority as a dynamic epistemological system capable of preserving the primacy of revelation while remaining adaptive to contemporary legal and societal transformations. The study concludes that the future development of Islamic jurisprudence requires an integrative approach that strengthens collective ijtihād, interdisciplinary engagement, and maqāṣid al-sharī'ah-oriented legal reasoning to ensure both normative authenticity and practical relevance.